Prevalence of Torus Palatinus for Forensic Anthropological Identification - Artanty, Dian; Artaria, Myrtati Dyah Dyah (Journal of Syiah Kuala Dentistry Society, 2024)
A torus palatinus is a bony prominence commonly located in the middle of the hard palate in the upper jaw. The prevalence of this phenomenon differs among various populations, which suggests that it could serve as a possible indicator for individual identification. This study aimed to examine the prevalence of torus palatinus in the Deuteromalayid and Protomalayid populations, encompassing individuals of both genders between the ages of 20 and 80 years. The research involved an observational non-metric analysis of 72 craniums obtained from the Department of Anatomy and Histology at Airlangga University. Out of the samples examined, a single skull (1.39%) from a 50-year-old male exhibited a torus palatinus.